High prevalence of multiple serotypes of pneumococci in patients with pneumonia and their associated risk factors. Issue 11 (26th April 2022) - Dhoubhadel, Bhim Gopal; Suzuki, Motoi; Ishifuji, Tomoko; Yaegashi, Makito; Asoh, Norichika; Ishida, Masayuki; Hamaguchi, Sugihiro; Aoshima, Masahiro; Yasunami, Michio; Ariyoshi, Koya; Morimoto, Konosuke
Abstract : Background: Multiple serotypes of pneumococci have epidemiological and clinical implications, such as the emergence of non-vaccine serotypes and the acquisition of antimicrobial resistance. Prevalence of multiple serotypes of pneumococci in adults and their risk factors are not known. Methods: We enrolled adult patients from age ≥15 years with radiologically confirmed pneumonia in four hospitals across Japan. Pneumococcal pneumonia was defined with a pneumococcal bacterial density of ≥10 4 /mL in sputum by lytA quantitative PCR, and serotypes were determined. Pneumonias with a single serotype were categorised as single-serotype pneumococcal pneumonia and with two or more serotypes as multiple-serotype pneumococcal pneumonia. Multivariable logistic regression was used to assess the risk factors. Results: 3470 patients (median age 77 years, IQR 65–85) were enrolled. Pneumococcal pneumonia was identified in 476 (18.3%, n=2605) patients. Multiple serotypes were detected in 42% of them. Risk of having multiple serotypes was low among patients who had received 23-valent pneumococcal polysaccharide vaccine (PPSV23) vaccines (adjusted OR 0.51 (95% CI 0.27 to 0.94)). Proportion of non-PCV7 PPSV23 serotypes in overall distribution of multiple serotypes was 67.4% (n=324/481) compared with 46.4% (n=128/276) in that of single serotypes (p=0.001). Serotypes 5, 9N/9L, 10A, 12/22/46, 17F and 35F were associated with multiple-serotype pneumonia, and serotypes 6A/6B, 23F, 11 and 6C/6D were associated with single-serotype pneumonia. Proportion of more invasive serotypes (serotypes 1, 5, 7F, 8) was significantly higher in multiple-serotype pneumonia (p=0.001). Conclusions: Multiple serotypes of pneumococci are common in sputum of adult patients with pneumonia. The risk of multiple-serotype pneumococcal pneumonia is lower than that of single-serotype pneumococcal pneumonia among PPSV23-vaccinated patients. Trial registration number: UMIN000006909.